Factors affecting punching speeds of hollerith operators. Mechanical factors outside the control of the operators - Majewski, T. R. (College of Aeronautics, 1954)
One of the major influences governing punching speeds is the operator's reaction to what she regards as the innate stiffness of the punch. This Note reviews those factors which are attributable to the machine rather than the operator, and seeks to assess their relative importance from the viewpoint of their effect on punching performance. On the basis of a number of tests using a standard keyboard under normal operating conditions and employing motion-study techniques, the following conclusions are reached respecting the influence on punching speeds of the various factors. 1. The stroke of the kay has very little influence on punching speeds 2. The spacing of the keys has an appreciable effect on punching speeds 3. The so-called 'stiffness' of the punch is often not stiffness in the mechanical sense, but is a physiological reaction in the operator to different key-top pads 4, A certain amount of variability of pressure is always inherent in the machine, and operators are, within certain pressure ranges, extremely sensitive to such variability. An Appendix to the Note describes the key-punch 'Pressure Pick-up' which was designed for the tests.